2010
DOI: 10.7454/mst.v13i1.496
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Production From Microalgae as a Promising Candidate for Biodiesel Production

Abstract: Recently, several strains of microalgae have been studied as they contain high lipid content capable to be converted to biodiesel. Fresh water microalgae Chlorella vulgaris studied in this research was one of the proof as it contained high triacyl glyceride which made it a potential candidate for biodiesel production. Factors responsible for good growing of microalgae such as CO 2 and nitrogen concentration were investigated. It was found that total lipid content was increased after exposing to media with not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
3
16
0
8
Order By: Relevance
“…This explained the relatively lower lipid and biodiesel contents under salt stress conditions. The data obtained in this investigation were in good agreement with results published by Widjaja (2009) who reported that the green microalga Chlorella vulgaris accumulated high lipid content when cultivated in nitrogen depletion condition (0.02 mg/l nitrate). Our results also went parallel with those obtained by Lardon et al (2009) who found that, the control of nitrogen stress during the culture and optimization of wet extraction led to maximum biodiesel production from the microalgal culture Chlorella vulgaris.…”
Section: Resultssupporting
confidence: 82%
“…This explained the relatively lower lipid and biodiesel contents under salt stress conditions. The data obtained in this investigation were in good agreement with results published by Widjaja (2009) who reported that the green microalga Chlorella vulgaris accumulated high lipid content when cultivated in nitrogen depletion condition (0.02 mg/l nitrate). Our results also went parallel with those obtained by Lardon et al (2009) who found that, the control of nitrogen stress during the culture and optimization of wet extraction led to maximum biodiesel production from the microalgal culture Chlorella vulgaris.…”
Section: Resultssupporting
confidence: 82%
“…Both studied Chlorella strains produced signifi cantly higher amounts of lipid when exposed to elevated CO 2 . This is consistent with the study of Widjaja [21], who reported that the lipid content of C. vulgaris increased with increasing CO 2 concentration. As microalgae form the basis of the food chain, changes in biochemical composition, including lipids, can alter their nutritional value, with consequences throughout the food chain.…”
Section: Discussionsupporting
confidence: 93%
“…Increasing atmospheric CO 2 concentration is commonly predicted to lead to changes in biochemical composition of microalgae [21,22]. Both studied Chlorella strains produced signifi cantly higher amounts of lipid when exposed to elevated CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The extraction result was then being evaporated and dissolved in an oven at a temperature of 100 ° C until a constant weight was obtained. The extra weight is expressed as the lipid weight in the material (Widjaja, 2010;Indarto, 2008). The collected data of lipid content was recorded and made a histogram.…”
Section: Lipid Content Measurementmentioning
confidence: 99%